Understanding The Identity of Women Wearing The Niqab in Relation To Extremist and Radical Stereotypes - Risa Aminatus Sholihah; Dinda Aufa Nur Fadhilah; Rahmania Diasti; Vrisko Putra Vachruddin (Yinyang: Jurnal Studi Islam Gender dan Anak, 2025)
Some people generally perceive that wearing the niqab is closely associated with extremist and radical groups. However, every individual has the right to choose how to dress according to their personal beliefs and values. This study discusses the relationship between the identity of women wearing the niqab and the perceptions linking them to extremist and radical groups. The identity of women wearing the niqab is often associated with the views and actions of such groups. The purpose of this article is to explore the legal arguments regarding the niqab based on the four schools of Islamic thought, to analyze the cultural concepts and interpretations of the niqab across different regions of the world, and to examine the relationship between the identity of women wearing the niqab from religious, social, and cultural perspectives. This study employs a literature review method, using data collected from national and international journal articles and analyzed through the interactive model of Miles, Huberman, and Saldana.  The findings reveal that the practice of wearing the niqab carries both positive and negative stereotypes. The negative stereotypes tend to portray the niqab as a marker of identity linked to extremist and radical groups. Meanwhile, several positive stereotypes are also commonly attributed to women who wear the niqab, such as piety and devotion, honor and dignity, wisdom and maturity, as well as serving as role models and sources of inspiration. It is important to understand that a person’s identity is not solely determined by their appearance or clothing. The identity of women wearing the niqab can be influenced by religion, community, and culture; however, not all women wearing the niqab are involved in extremism or radicalism. Every individual has the freedom to express their identity in a way that reflects their beliefs, as long as it does not violate the law or human values.